PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KANTOR BPN KAB. PROBOLINGGO - Rozi, Fathur; Cahyono, Rudi (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Abstract The land registration program through complete systematic land registration (PTSL) which targets land registration throughout Indonesia is expected to be completed in 2025. This is the first land registration activity to be carried out simultaneously. How is it implemented and what obstacles are faced by BPN Kab. Probolinggo in implementing the PTSL program. Apart from that, this research also aims to identify steps that can be taken to overcome these obstacles and increase the efficiency of PTSL implementation. This research uses an empirical juridical approach. Data was obtained through field case studies, literature and policy analysis relevant to the PTSL Program. This research found that PTSL has an important role in providing legal certainty and protection of land rights in Indonesia. However, obstacles faced include limited human resources, geographic challenges, and administrative complexity. To overcome this, it is necessary to increase recruitment and training of human resources, use of information technology, collaboration between related parties, and a holistic, technology-based approach. By overcoming these obstacles, PTSL can be implemented more efficiently and provide greater benefits in providing legal certainty and protection of land rights in Indonesia. Keywords: Land Registration, PTSL Program, Land Certificate